Exact solutions for geophysical flows with discontinuous variable density and forcing terms in spherical coordinates - Jifeng Chu (Research Platform Erwin Schrödinger International Institute for Mathematical Physics (ESI), Research Platforms, University of Vienna); Calin Iulian Martin (Research Platform Erwin Schrödinger International Institute for Mathematical Physics (ESI), Research Platforms, University of Vienna); Kateryna Marynets (Research Platform Erwin Schrödinger International Institute for Mathematical Physics (ESI), Research Platforms, University of Vienna) (Applicable Analysis, 2023)
The abstract is available here: https://uscholar.univie.ac.at/o:2007828 The abstract is available here: https://uscholar.univie.ac.at/o:2007828